Indonesian Bankruptcy Law: Revisited - Wijantini, . (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2008)
One of the key challenges in fnancial distress resolution is to fnd the way to renegotiate the debts. Financial troubled firms may apply either court or out-of-court resolution process. Under court supervision, frms have to follow Indonesian bankruptcy law which ofers a moratorium on debt repayment through a system of court supervision and liquidation proceedings. Alternatively, frms may apply out-of-court workout. This paper is written to examine process of both resolutions, problem in executing the law and the reasons for least likelihood of fling court solution in Indonesia. In addition, it shows study on bankruptcy fling in East Asia countries.